2007
DOI: 10.1158/0008-5472.can-06-2486
|View full text |Cite
|
Sign up to set email alerts
|

p38 Mitogen-Activated Protein Kinase Pathway Is Involved in Protein Kinase Cα–Regulated Invasion in Human Hepatocellular Carcinoma Cells

Abstract: Protein kinase CA (PKCA) has been suggested to play an important role in tumorigenesis, invasion, and metastasis. In this study, we investigated the signal pathways selectively activated by PKCA in human hepatocellular carcinoma (HCC) cells to determine the role of mitogen-activated protein kinases (MAPK) in PKCA-mediated HCC migration and invasion. A stable SK-Hep-1 cell clone (siPKCA-SK) expressing DNA-based small interfering RNA (siRNA) PKCA was established and was then characterized by cell growth, migrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 41 publications
4
70
0
Order By: Relevance
“…It is possible that in BRCA1-IRIS-silenced cells the induction of replication arrest (ElShamy and Livingston, 2004) activates p38MAPK, as was shown recently (Im and Lee, 2008;Rodrı´guez-Bravo et al, 2007). However, in undamaged BRCA1-IRIS overexpressing cells, perhaps p38MAPK is activated to induce cell survival and/or motility (Suarez-Cuervo et al, 2004;Demuth et al, 2007;Hsieh et al, 2007;Junttila et al, 2007). Alternatively, as p-p38MAPK phosphorylates HuR in the nucleus and enhances its cytoplasmic translocation (Gorospe, 2003;Tran et al, 2003;Lafarga et al, 2009), it is possible that in undamaged cells, this is how BRCA1-IRIS induces HuR cytoplasmic translocation (this study).…”
Section: Brca1-iris Induces Proliferation Of Geno-/cell-toxic Damagedmentioning
confidence: 88%
“…It is possible that in BRCA1-IRIS-silenced cells the induction of replication arrest (ElShamy and Livingston, 2004) activates p38MAPK, as was shown recently (Im and Lee, 2008;Rodrı´guez-Bravo et al, 2007). However, in undamaged BRCA1-IRIS overexpressing cells, perhaps p38MAPK is activated to induce cell survival and/or motility (Suarez-Cuervo et al, 2004;Demuth et al, 2007;Hsieh et al, 2007;Junttila et al, 2007). Alternatively, as p-p38MAPK phosphorylates HuR in the nucleus and enhances its cytoplasmic translocation (Gorospe, 2003;Tran et al, 2003;Lafarga et al, 2009), it is possible that in undamaged cells, this is how BRCA1-IRIS induces HuR cytoplasmic translocation (this study).…”
Section: Brca1-iris Induces Proliferation Of Geno-/cell-toxic Damagedmentioning
confidence: 88%
“…For example, constitutive p38 MAPK activity has been confirmed to be crucial for the maintenance of breast cancer invasive phenotype via the stabilization of uPA and uPAR expression (25). Other studies have also revealed the positive regulatory role of p38 or ERK1/2 MAPK pathways in the invasive phenotype of human hepatocellular carcinoma cells and oral squamous cell carcinoma cells, respectively (26,27). However, cisplatin and cannabinoids have been shown to exert their anti-invasive properties on human cervical carcinoma cells (HeLa and C33A) and human lung carcinoma cells (A549) via the activation of the p38 and ERK1/2 MAPK pathways, respectively (21,12).…”
Section: Discussionmentioning
confidence: 99%
“…As TPA can substitute for naturally occurring diacylglycerol (DAG) for an effective activation of PKC, it is used as a classical skin tumour promoter 20 . PKCs have been implicated as mediators for MAPK/p38 activation 21,22 . In addition to mediating TPA-induced skin cancer, p38 is also critical for UV-induced skin carcinogenesis 17,23,24 .…”
Section: Discussionmentioning
confidence: 99%